2019
DOI: 10.20897/femenc/5915
|View full text |Cite
|
Sign up to set email alerts
|

Glocalised Motherhood: Sociality and Affect in Migrant Mothers’ Online Communities

Abstract: This article explores the importance of relationships between migrant mothers in Australia through the lens of Facebook groups created by and for migrant mothers, referred to here as glocalised maternal communities. The combination of migration and motherhood creates a dual rupture in mothers' social networks, leading to isolation and emotional challenges. Drawing on thematic analysis of interviews conducted with 41 mothers from a range of migrant communities (including Indian, Malaysian, Swedish, German, Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Although many playgroups use social media to communicate about play (McLean et al, 2017), this use evolved organically, and has never been the only means for families to get ideas for play. Research has found that parents’ (Haslam et al, 2017), including migrant mothers (Williams Veasely, 2019) and new mothers (Archer & Kao, 2018), use of social media enables social connections, friendship and parenting support, however, the extent to which social media use in playgroups offers similar types of social support for children’s play-based learning is unclear. The pandemic conditions, therefore, create a unique opportunity to understand the enablers and barriers playgroup families face in the provision of play-based remote-learning.…”
Section: Introductionmentioning
confidence: 99%
“…Although many playgroups use social media to communicate about play (McLean et al, 2017), this use evolved organically, and has never been the only means for families to get ideas for play. Research has found that parents’ (Haslam et al, 2017), including migrant mothers (Williams Veasely, 2019) and new mothers (Archer & Kao, 2018), use of social media enables social connections, friendship and parenting support, however, the extent to which social media use in playgroups offers similar types of social support for children’s play-based learning is unclear. The pandemic conditions, therefore, create a unique opportunity to understand the enablers and barriers playgroup families face in the provision of play-based remote-learning.…”
Section: Introductionmentioning
confidence: 99%